Temporal evolution of digital health communication in Rheumatoid Arthritis: A longitudinal NLP analysis of reddit discussions (2018–2024) - Naisarg Patel; Rajesh Sharma; Prakash Lingasamy; Vino Sundararajan; Sajitha Lulu S; Vijayachitra Modhukur (PLoS ONE, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune condition characterized by joint pain, fatigue, and reduced quality of life. Although pharmacological interventions, such as non-steroidal anti-inflammatory drugs (NSAIDs) and disease-modifying antirheumatic drugs (DMARDs), address physical symptoms, the psychological and emotional challenges associated with RA are frequently neglected. Social media platforms, particularly Reddit, have emerged as significant venue for patients to share experiences and seek support, a trend that has intensified during the COVID-19 pandemic. This study examined six years (2018–2024) of discussions from the r/rheumatoid and r/rheumatoidarthritis subreddits, encompassing 22,537 posts and 276,209 comments. Natural language processing (NLP) techniques were implemented to analyze sentiment, emotions, discussion topics, drug mentions, and hyperlink-sharing patterns across three phases: pre-COVID, during COVID, and post-COVID. The analysis indicated that comments were predominantly positive, whereas posts exhibited increased negativity following the onset of COVID-19. Fear and sadness were prevalent in posts, while comments frequently conveyed joy, underscoring the community’s supportive nature. Topic modeling identified recurring discussions concerning treatment efficacy, mental health, and pandemic-related disruptions. Methotrexate emerged as the most frequently mentioned medication, with notable emotional variation during the pandemic. Hyperlink patterns suggested an increasing reliance on medical and academic sources, reflecting patients’ need for reliable information. These findings illustrate how online communities capture evolving patient experiences and unmet needs. Insights from such discussions can inform healthcare providers, policymakers, and public health communicators in developing patient-centered strategies that address both the emotional and informational dimensions of RA care.